Hierarchical Control and its Key Technologies for Power Quality Enhancement in Micro-grids - MENG Lexuan; ZHAO Xin; Mehdi SAVAGHEBI (Kongzhi Yu Xinxi Jishu)
Wide application of power electronic converters enables power quality regulation using grid-connected inverters of distributed generators (DG), but it also brings more challenges on the control and management of those devices. Based on the existing research findings and the future power quality requirements in microgrids and distribution networks, it proposed a three-layer control and management scheme, and summarized the essential technics and challenges in each layer. A number of research issues are still open to be investigated, and the future research trend was discussed in the final section of the paper.